GACOR : GAYA AKSI CEGAH OBATI DAN RUJUK CEGAH SEBELUM TERLAMBAT - Lestari, Tutik; Surasno, Diah Merdekawati; Ramli, Ramli; Daud, Ruslia; Aulia, Rifanda; Sumarto, Sabaria; Diman, Tiara; Langasa, Siti AIgina; Sahsun, Darmila; Aldjokdja, Retno Kartika; Manteto, Tiara; M, Fitra Tunisyah; Hasan, Risma Hi; Salim, Nurmai; Minggu, Musdalifa; Laego, Riyanti; Fataha, Fadila S.Hi. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Blood sugar testing is a crucial step in the early detection of non-communicable diseases, particularly diabetes mellitus. This activity serves as a preventative strategy to determine the community's health status early before serious complications arise. In its implementation, blood sugar testing activities are carried out directly with the community through a promotive and educational approach. The community is provided with an understanding of diabetes risk factors, the importance of a healthy lifestyle, and how to recognize early symptoms that often go unnoticed. The activity involved 40 participants over three days, in accordance with the monthly agenda in the village. The results showed that some participants had blood sugar levels exceeding the normal threshold (>200 mg/dL), as many as 4 people, requiring follow-up in the form of further examinations and referrals to health facilities. Furthermore, this activity also succeeded in raising participants' awareness to more regularly check their health and start adopting a healthy diet and regular physical activity.